Investigation of integrated time nanosecond pulse irreversible electroporation against spontaneous equine melanoma - Fesmire, Chris C.; Peal, Bridgette; Ruff, Jennifer; Moyer, Elizabeth; McParland, Thomas J.; Derks, Kobi; O’Neil, Erin; Emke, Carrie; Johnson, Brianna; Ghosh, Shatorupa; Petrella, Ross A.; DeWitt, Matthew R.; et al. (Frontiers in Veterinary Science, 2024)
Introduction Integrated time nanosecond pulse irreversible electroporation (INSPIRE) is a novel tumor ablation modality that employs high voltage, alternating polarity waveforms to induce cell death in a well-defined volume while sparing the underlying tissue. This study aimed to demonstrate the in vivo efficacy of INSPIRE against spontaneous melanoma in standing, awake horses. Methods A custom applicator and a pulse generation system were utilized in a pilot study to treat horses presenting with spontaneous melanoma. INSPIRE treatments were administered to 32 tumors across 6 horses and an additional 13 tumors were followed to act as untreated controls. Tumors were tracked over a 43–85 day period following a single INSPIRE treatment. Pulse widths of 500ns and 2000ns with voltages between 1000 V and 2000 V were investigated to determine the effect of these variables on treatment outcomes. Results Treatments administered at the lowest voltage (1000 V) reduced tumor volumes by 11 to 15%. Higher voltage (2000 V) treatments reduced tumor volumes by 84 to 88% and eliminated 33% and 80% of tumors when 500 ns and 2000 ns pulses were administered, respectively. Discussion Promising results were achieved without the use of chemotherapeutics, the use of general anesthesia, or the need for surgical resection in regions which are challenging to keep sterile. This novel therapeutic approach has the potential to expand the role of pulsed electric fields in veterinary patients, especially when general anesthesia is contraindicated, and warrants future studies to demonstrate the efficacy of INSPIRE as a solid tumor treatment.